Efficacy and safety of phytoestrogens in the treatment of perimenopausal and postmenopausal depressive disorders: A systematic review and meta‐analysis. Issue 10 (3rd June 2021) - Li, Jieyun; Li, Huijuan; Yan, Peijing; Guo, Liping; Li, Jingwen; Han, Jiani; Qiu, Jie; Yang, Kehu
Abstract: Background: Depression is one of the most common and specific symptoms among menopausal women, leading to significant personal, family, and economic burdens. Some studies have shown that phytoestrogens can help relieve symptoms of depression. Objectives: This systematic review and meta‐analysis aim to assess the efficacy and safety of phytoestrogens in treating depression among menopausal women. Methods: A comprehensive search for relevant studies published until November 25, 2020, was conducted in PubMed, the Cochrane Library, Chinese Biomedical Literature Database, Web of Science, and EMBASE. Statistical analyses were performed with R 4.0.3.and Review Manager 5.4. Results: 2183 studies were identified and 10 studies with 15 independent reports were included, involving 1248 participants. The quality of the four studies was assessed as high risk, six studies were assessed as unclear. The analyses conducted according random effects model indicated the significant positive effect on depressive symptoms for postmenopausal women compared with the placebo (SMD = −0.62; 95% CI = −1.13 to −0.12; Q  = 45.62, df  = 14, P  < .01; I 2  = 79%). The low dose phytoestrogens (25 mg/d ≤ dose ≤ 100 mg/d) have better effectiveness (SMD = −0.52; 95% CI = −0.85 to −0.20; I 2  = 79%, P < .01) than high dose (dose > 100 mg/d) and ultralow dose (0 < dose < 25 mg/d), but showed no statistical significance (Q = 0.81 df  = 2, P  = .67). Isoflavones had better effectiveness (SMD = −0.48; 95% CI = −0.75 to 0.21; I 2  = 75%, P  < .01) than lignans of phytoestrogens (SMD = −0.22; 95% CI = −0.37 to 0.08; I 2  = 0%, P  = .96). The duration of intervention affects the efficacy of phytoestrogens ( β  = −0.03; 95% CI: [−0.05, 0.00]; P  = .045). The effectiveness varies in regions. The adverse reactions frequently reported were gastrointestinal symptoms and cold or upper respiratory tract infection. Conclusions: Phytoestrogen can relieve depression symptoms among menopausal, especially for postmenopausal women who take low doses(25 mg/d ≤ dose ≤ 100 mg/d) of phytoestrogens for a long‐term duration. Although mild adverse reactions have been reported, phytoestrogen could be considered as a complementary treatment for postmenopausal depression.